2015
DOI: 10.1515/remav-2015-0040
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modeling Of Office Rent In Selected Districts Of Abuja, Nigeria

Abstract: This study examined the drivers of office rents in selected districts of Abuja, Nigeria. These districts are Asokoro, Maitama and Utako. Primary and secondary data were utilized for the study. Primary data include office rental levels and office space data in the study areas for the period 2001-2012, and were obtained through structured questionnaires administered to real estate surveying and valuation firms which are active in the commercial property markets in the study areas. Secondary data for the study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Ojetunde also found that interest rate has a significant negative correlation with housing rents while an insignificant negative correlation was found between inflation rate and housing rents. In addition to this, Udoekanem et al (2015) revealed that although inflation rate granger causes rental movements, the authors, however, found evidence that inflation rate does not have a significant influence on rental values of office property in Abuja, Nigeria. This lack of consensus in the literature regarding the correlation between the identified macroeconomic variables and the real property market could be attributed to factors such as differences in property markets/geographical locations, varying timeframes and fluctuating economic conditions.…”
Section: Findings and Discussionmentioning
confidence: 85%
“…Ojetunde also found that interest rate has a significant negative correlation with housing rents while an insignificant negative correlation was found between inflation rate and housing rents. In addition to this, Udoekanem et al (2015) revealed that although inflation rate granger causes rental movements, the authors, however, found evidence that inflation rate does not have a significant influence on rental values of office property in Abuja, Nigeria. This lack of consensus in the literature regarding the correlation between the identified macroeconomic variables and the real property market could be attributed to factors such as differences in property markets/geographical locations, varying timeframes and fluctuating economic conditions.…”
Section: Findings and Discussionmentioning
confidence: 85%
“…In addition, clients influence valuation accuracy in so many ways amongst which are "shopping for valuer" that will apportion the desired value to the appraisal, threatening to withhold payment of fees and closing the door on future patronage (Amidu and Aluko, 2007). Several related studies (Effiong and Mendie, 2019;Ayedun et al, 2010;Udoekanem, 2018) have established the existence of client pressure in the Nigerian valuation industry and how it corrodes the objectivity of valuers as they upwardly adjust values to suit their clients. Besides, a critical review of the studies carried out locally showed that they focussed more on the property markets in Southern Nigeria (Ogunba and Ajayi, 1998;Ogunba, 2004;Ajibola, 2010;Babawale and Ajayi, 2011;Oduyemi et al, 2016;Abidoye and Chan, 2018) in terms of geographical scope and none tested the ability of valuation to predict transaction price in the residential property market apart from Ogunba (2004) and Abidoye and Chan (2018)…”
Section: Review Of the Causes Of Valuation Inaccuracymentioning
confidence: 99%
“…Valuation accuracy is measured through the margin of error principle. The margin of error is the bracket of acceptable percentage error (PE) in valuations (Crosby, 2000;Udoekanem, 2018;Dou et al, 2021). Quantitatively, PE in valuation is measured as the ratio of the absolute difference between the actual price of the property realised at the market and valuation to the actual price, expressed as a percentage.…”
Section: Measurement Of Valuation Accuracymentioning
confidence: 99%
“…Assessing rental patterns of commercial real estate helps in guiding investors to make better investment decisions. It can be used to predict the dynamics of the real estate market (Born & Pyhrr, 1994;Tonelli et al, 2004;Udoekanem et al, 2015b). The parameters for measuring rental performance are most often seen in the discounted cash flow models for property appraisals (Boon & Higgins, 2007).…”
Section: Baltic Journal Of Real Estate Economics and Construction Man...mentioning
confidence: 99%
“…The study revealed a progressive upward movement in rental values of office premises which by implication indicated that office rent in Minna performed strongly as a hedge against inflation. In another research, Udoekanem et al (2015b) attempted the modelling of office rents for the Asokoro, Maitama, and Utako districts of Abuja. The study revealed that the real GDP had a significant influence and remained the major driver of all commercial property rents throughout the study areas.…”
Section: Commercial Real Estate Rental Studiesmentioning
confidence: 99%